Medieval English Benedictine liturgy - Harper, S; Roper, Sally Elizabeth (1989)
﻿ By comparison with its secular counterpart, the liturgy of English medieval monasteries has received little attention. This thesis explores one aspect of the liturgy of some of the wealthiest and most influential foundations in England - the Benedictine houses. It covers the formation and proliferation of 'votive' observances, recited as additions to or replacements for the major calendar observances. Evidence is drawn from over fifty manuscripts, dating from the Benedictine reform of the tenth century to the eve of the Dissolution in the sixteenth century. Some thirty monasteries are represented, with particular reference to the practices of Winchester, St Albans, Worcester and St Mary's, York. Part One examines the precedent for appended observances in The Rule of St Benedict (c.540), and the interpretation of this document by the Carolingian reformer Benedict of Aniane (c.750-821). Votive practices in the first English monastic customary, Regularis Concordia (c.970), and other devotional sources of a similar date are analysed. Part Two deals with the proliferation of three major observances after the Conquest - the daily votive office, recited as an appendage to the regular hours, the weekly commemorative office, which served as a replacement for the ferial office, and the independent antiphon (in particular Salve regina), recited or sung after Compline. The structure, adoption and devotional characteristics of each observance are examined, with particular reference to the predominantly Marian bias of much of the repertory. The second volume contains liturgical texts and related analytical tables, a descriptive catalogue of sources, transcriptions of Marian antiphons from the Worcester Antiphoner (c. 1230) and a comparison of eight versions of Salve regina.